2019
DOI: 10.1101/806992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular ATP and CD39 activate cAMP-mediated mitochondrial stress response to promote cytarabine resistance in acute myeloid leukemia

Abstract: Relapses driven by chemoresistant leukemic cell populations are the main cause of mortality for patients with acute myeloid leukemia (AML). Here, we show that the ectonucleotidase CD39 (ENTPD1) is upregulated in cytarabine (AraC)-resistant leukemic cells from both AML cell lines and patient samples in vivo and in vitro. CD39 cell surface expression and activity is increased in AML patients upon chemotherapy compared to diagnosis and enrichment in CD39-expressing blasts is a marker of adverse prognosis in the c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…High mitochondrial ETC or OXPHOS activities were repeatedly linked to Venetoclax-or chemotherapy-resistance in AML (13)(14)(15)17) or other cancers (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High mitochondrial ETC or OXPHOS activities were repeatedly linked to Venetoclax-or chemotherapy-resistance in AML (13)(14)(15)17) or other cancers (18).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunctions can induce the integrated stress response and ROS production, important features of normal or AML stem cells (12). Conversely, mitochondrial fitness and high OXPHOS metabolism have been implicated in resistance to BCL2 inhibitors or conventional chemotherapy (13)(14)(15)(16)(17)(18). Accordingly, inhibitors of mitochondrial respiration were proposed to constitute a novel type of Research.…”
Section: Introductionmentioning
confidence: 99%
“…Chemoresistance is also mediated by interactions between AML cells and their microenvironment ( 85 87 ). It has been recently demonstrated that an inflammatory and immune interferon-γ signature is associated with chemoresistance ( 88 ).…”
Section: Bench Researchmentioning
confidence: 99%
“…These three metabolites are mainly involved in ROS management through glutathione biosynthesis, folate cycle and transulfuration pathway. It is known that AraC leads to an increase in ROS content in vivo, through enhanced OxPHOS status 4,42 . An increase in these three metabolites in most organs support an adaptation of murine niches to this oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these metabolites are markedly impactful in our metabolic signature from human patient plasma. The OxPHOS status is described as critical to many drug resistances in AML 4,11,42 . Accordingly, plasma is a tissue of interest for biomarker of the oxidative status of patient blasts to improve management of AML patients.…”
Section: Discussionmentioning
confidence: 99%